Migraine in Women - Broner, Susan W.; Bobker, Sarah; Klebanoff, Louise (Seminars in Neurology, 2017)
Migraine is one of the most common neurological disorders, affecting women disproportionally at a rate of 3:1. Prior to puberty, boys and girls are equally affected, but the female preponderance emerges after puberty. Migraine pathophysiology is not fully understood, and although the hormonal effect of estrogen is significant, other factors are at play. This article will focus on the hormonal influence on migraine in women. Here we review our most recent understanding of migraine and menstrual migraine, including epidemiology, pathophysiology, and treatment strategies for this challenging disorder, as well as migraine during pregnancy, postpartum period, breastfeeding, perimenopause, and menopause. We also review the risks and benefits of exogenous hormone use in this population and discuss stroke risk in women with migraine aura. By understanding these aspects of migraine in women, we hope to arm practitioners with the knowledge and tools to help guide treatment of this debilitating disorder in this large population.
Keywords: hormones; menstrual migraine; pregnancy; contraceptives; stroke